Adaptation Study of the Statistical Anxiety Scale on a Bangladesh Sample - L. Paul; T. Parveen; O. Ahmed; R. Aktar (University of Sofia, 2018)
Due to unavailability of a developed or adapted instrument for statistical anxiety in Bangladesh context, the present study was designed to adapt the Statistical Anxiety Scale (SAS) (Vigil-Colet et al., 2008). Adaptation procedure was done by following guidelines of the International Test Commission (ITC). The translated SAS was administered on a sample of 238 students from the Chittagong University who were selected though non-probability sampling techniques. The internal consistency reliabilities, content validity, and construct validity were determined for assessing the psychometric properties of the Bangla SAS. The item-total correlations, exploratory factor analysis, confirmatory factor analysis, correlation coefficients among the SAS and its subscales, Chronbach's Aplhas, split-half reliability, composite reliability suggested that the Bangla SAS would be a psychometrically sound measure to apply in Bangladesh context.